The Influence of the Problem Based Learning (PBL) Model on Student Learning Motivation - Bahtiar Amin Zuhri (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to determine the effect of implementing the Problem-Based Learning (PBL) model on the learning motivation of seventh-grade students at SMP Negeri 2 Cilongok. This quantitative study uses a quasi-experimental design involving two groups, namely the experimental group that implements PBL and the control group that uses conventional learning. Learning motivation data were collected through pre-tests and post-tests. The results showed no significant difference in initial learning motivation between the two groups. However, after implementing PBL, there was a significant increase in learning motivation among students in the experimental group compared to the control group. The average learning motivation of the experimental group increased to 98.46, while the control group reached 82.53. The statistical test results (t-count = 6.953 > t-table = 1.67) confirmed a significant difference. These findings indicate that PBL is effective in increasing students' learning motivation, supported by the characteristics of PBL that actively involve students in problem-solving, group work, and the development of critical thinking skills. Based on the research results, it is recommended that PBL be used as a learning strategy to increase students' learning motivation.